A Study of Soluble Proteins(Spl and Sp2) Effect of extracted from Proteus mirabilis on the Activity of Superoxide Dismutase,SOD in the Sera of albino rabbit - Al-Abd el waheed, L.S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The a i m of the present study is to shed some light on the imm u nol ogica l effect of so lub l e protei ns extracted from Proteu mirabilis th rough em ployi ng t he level of the en zy mati c activity of Superoxide Dismutase,SOD. The olublc proteinsÂ·Sp I and Sp2,were extracted by usi ng th e lysosyme enzyme .The rabbits were divided into three groups ,the fir t one was injected with Spl, the second with Sp2 for four weeks a nd the th ird one was the control group. The results reveal ed tha t enzymatic activ i ty of Superox ide Dismutase,SOD was sign ificantly increased in the fi ft h weekes of injection with S p I com pa red with contro l group.Th e sam e effects of the Sp2 were obser ed in specific enzymatic activ i ty of Su peroxide Dismutase,SOO.Therfore,the extracted soluble proteins had an effect on the innate immune respon e of the rabbits.